The Triumph of the Second Leaders: Ahmad Khatib and Rashīd Riḍā in Islamic Reform in Indonesia - Jajat Burhanudin (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
The advent of Islamic reform in Indonesia at the turn of the 20th century is to be attributed to two scholars or called the second Muslim leaders. They were Ahmad Khatib in Mecca and Rashīd Riḍā in Cairo. Ahmad Khatib was an intellectual leader of mainly Malay-Indonesian section of Jawa (Southeast Asians Muslims) in Mecca when the Islamic reform began to be voiced by Cairo ‘ulama, Muḥammad ‘Abduh and Rashīd Riḍā. One crucial point to discuss in this article is that the two scholars shared similar religious thoughts, which hold a determining role in the development of Islamic reform, much more than the role of Muḥammad ‘Abduh, the first leader of the movement. As can be gleaned from Ahmad Khatib’s works and his intellectual orientation, as well as from the fatwas of Rashīd Riḍā in al-Manār, both scholars emphasized the primacy of pristine Islam (salāf), different from the thought of ‘Abduh. In fact, it was in the hands of Ahmad Khatib’s students that the Islamic reform reached wider audiences in Indonesia and Southeast Asia. At the same time, the early 20th century also witnessed the mounting request for fatwas to Rashīd Riḍā in al-Manār, which greatly contributed to the transmission of reform ideas from Cairo to the region.